Rating attributes toolkit for the residential property market - Renigier-Bilozor, Malgorzata; Wisniewski, Radoslaw; Bilozor, Andrzej (International Journal of Strategic Property Management, 2017)
The growing significance of the real estate market prompts investors to search for factors and variables which support cohesive analyses of real estate markets, market comparisons based on diverse criteria and determination of market potential. The specificity of the real estate market is determined by the unique attributes of property. The authors assumed that developing real estate market ratings identifies the types of information and factors which affect decision-making on real estate markets. The main objective of real estate market ratings is to create a universal and standardized classification system for evaluating the real estate market. One from the most important problem in this area is collection of appropriate features of real estate market and development dataset. The main problem involves the selection and application of appropriate features, which would be relevant to the specificity of information related to the real estate market and create a kind of coherent system aiding the decision-making process. The main aim of this study is to elaboration set of variables (knowledge platform) that were used to elaborate the real estate market ratings. The results lead to obtain the necessary set of features that constitute essential information which describes the situation on the local real estate market.